PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN (Kasus Pada Hotel Ratu Mayang Garden Pekanbaru) - Aula Wendi Saputra; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of Work Environment and Individual Characteristics of Employee Performance (case at Hotel RatuMayang Garden Pekanbaru). Work Environment as variable (X1) Individual Characteristics as variable (X2) and Performance as (Y).The method in this research is descriptive and quantitative by using SPSS 20 program. The sample used is 92 employees consisting of 10 departments. To determine the sample using census research method.Technique of collecting data through questionnaire.The results of analysis using multiple linear regression, t test, and test f. It can be seen that work environment variables significantly influence employee performance, characteristic have an effect on signifikan to employee performance, and work environment and characteristic of individual have significant effect to employee performance.Keywords: Work Environment, Individual Characteristics, Performance